Research trends and hotspots in gastric carcinoma associated exosome: a bibliometric analysis - Liu, Chunqiu; Guo, Honglei; Jin, Fangzhou (Frontiers in Oncology, 2024)
BackgroundStomach cancer is considered the fifth most common cancer worldwide. This study utilized bibliometric analysis to construct a visualization map of the relationship between stomach cancer and exosomes, aiming to reveal research trends and emerging themes, and provide direction for future research.MethodRetrieve relevant literature on gastric cancer exosomes in the Web of Science Core Collection (WoSCC) over the past 25 years according to search criteria, and conduct bibliometric and visualization analysis using bibliometric software VOSviewer and CiteSpace.ResultsThis study included a total of 727 articles, with an overall increasing trend in annual publication output. There were 68 countries involved, with China having the largest number of publications followed by the United States. A total of 957 research institutions were involved, with most of the top 10 institutions in terms of publication output being universities in China. The top 5 journals are Molecular Cancer, Cell death & disease, Cancers, International journal of molecular sciences, and Frontiers in oncology. A total of 4529 authors were involved, with 5 authors having a publication output of no less than 13 articles. A total of 35516 references were cited, with a total number of citations. The top publication is “Exosome-mediated transfer of mRNAs and microRNAs is a novel mechanism of genetic exchange between cells”.ConclusionOver the past 25 years, researchers have been dedicated to studying the field of exosomes related to gastric cancer, and research in this area is currently progressing steadily. Based on previous studies, exosomes in gastric adenocarcinoma serve as biomarkers, potential therapeutic targets, and post-resistance treatment, which represents current hotspots and emerging frontiers in research.